Transcripts of Anthocyanidin Reductase and Leucoanthocyanidin Reductase and Measurement of Catechin and Epicatechin in Tartary Buckwheat - Yeon Bok Kim; Aye Aye Thwe; YeJi Kim; Xiaohua Li; Jin Woong Cho; Phun Bum Park; Mariadhas Valan Arasu; Naif Abdullah Al-Dhabi; Sun-Ju Kim; Tastsuro Suzuki; Kwang Hyun Jho; Sang Un Park (The Scientific World Journal)
Anthocyanidin reductase (ANR) and leucoanthocyanidin reductase (LAR) play an important role in the monomeric units biosynthesis of proanthocyanidins (PAs) such as catechin and epicatechin in several plants. The aim of this study was to clone ANR and LAR genes involved in PAs biosynthesis and examine the expression of these two genes in different organs under different growth conditions in two tartary buckwheat cultivars, Hokkai T8 and T10. Gene expression was carried out by quantitative real-time RT-PCR, and catechin and epicatechin content was analyzed by high performance liquid chromatography. The expression pattern of ANR and LAR did not match the accumulation pattern of PAs in different organs of two cultivars. Epicatechin content was the highest in the flowers of both cultivars and it was affected by light in only Hokkai T8 sprouts. ANR and LAR levels in tartary buckwheat might be regulated by different mechanisms for catechin and epicatechin biosynthesis under light and dark conditions.